Things for thought – a creative toolkit to explore belonging. Issue 1 (31st May 2021) - Zino, Imogen; Nakarada-Kordic, Ivana; Smith, Valance; Reay, Stephen
Abstract: This paper describes the development of a creative toolkit - Things for thought – designed as a research probe that engages participants through a guided object-based exploration to help them better understand what belonging might mean to them. The toolkit draws on the Māori (indigenous people of Aotearoa New Zealand) creation narrative and uses engagement (via haptic interaction with physical objects), connection (with others by working collaboratively to subjectively identify similarities/differences), and discussion (using abstract physical objects, questions, and inclusive discussion techniques). Things for thought was designed to facilitate engagement between people from a wide range of communities. It uses Māori narrative and cultural values to help people understand and enhance connection to place and community. By using an inclusive cultural framework and a shared language (touch), an opportunity for innovative discussion around the topic of belonging, with the ultimate purpose of designing with socially inclusive communities was created. Plans are to test this toolkit in a range of settings including facilitating community discussions. We imagine that the toolkit could supplement co-creation workshops, workplace interactions, and be used in any context in which an in-depth understanding of oneself and others is useful.